Inovasi Minuman Herbal Berbasis Limbah Kulit Jeruk Dan Bunga Telang Sebagai Upaya Pemanfaatan Sumber Daya Alami - Fais Irawan; Mizael Demak Sitohang; Epelima Sinaga; Kevin Lejon Simamora; Agnes Dea Lita Br Sitepu; Putri Kemala Dewi Lubis (Jurnal Ilmiah Wahana Pendidikan, 2026)
This research aims to develop an innovative herbal drink based on orange peel and butterfly pea flower waste as an effort to utilize abundant local natural resources while supporting the strengthening of the creative economy and environmental sustainability. Orange peel waste from the food industry is used as a source of bioactive compounds, while butterfly pea flowers act as a natural dye and source of antioxidants, thereby increasing the functional and aesthetic value of the product. The research used an experimental method with an exploratory qualitative approach through the stages of cleaning, drying, grinding, mixing, formulation in tea bags, and sensory testing including color, aroma, taste, and clarity of the brew. The results show that the combination of orange peel and butterfly pea flowers produces a herbal drink with an attractive purplish blue color, a refreshing citrus aroma, a mild taste, and the potential to provide health benefits through antioxidant activity. This waste utilization model reflects the application of a circular economy because it is able to reduce organic waste, increase the economic value of waste materials, and open up opportunities for the development of superior products for MSMEs and the regional tourism sector. With the support of branding strategies, environmentally friendly packaging, and digital promotions that emphasize the values ​​of health, sustainability, and local wisdom, this herbal tea product has the potential to develop as a competitive creative commodity.